An investigation of stabilization and inhibition strength of the asphaltene inhibitors by viscometric method. Issue 19 (1st October 2016) - Dehaghani, A. H. Saeedi; Shadman, M. M.; Ahmadi, S.
ABSTRACT: Using inhibitors is one of the methods to prevent asphaltene formation. In the present work, we investigated the effects of three types of inhibitors on the onset of asphaltene precipitation using the viscometric method. Also in this study, a new concept called "effective adsorption point" of the inhibitor was proposed in order to determine the stabilization (dispersion) strength, by measuring the shear effects of asphaltene aggregates. The results showed that the amount of adsorbed inhibitor on the surface of asphaltene micelles, together with stabilization strength, started to increase with increasing inhibitor concentration. The results also revealed that there is a strong agreement between the calculated volume fraction of suspended particles and the effective adsorption point.